2009
DOI: 10.1017/s1356186309009699
|View full text |Cite
|
Sign up to set email alerts
|

Jahangir as Francis Bacon's Ideal of the King as an Observer and Investigator of Nature

Abstract: The Mughal Empire is paradigmatic in many of its formulations, and it is epitomised in the persons of its first six padshahs or emperors. The Great Mughals, Grao Mogor, Grand Mogul, Großmogul or Groote Mogul, as the padshahs were known in Europe, have been considered as paragons of rulership. In critical appraisals, which were the prevailing view in the seventeenth and eighteenth centuries, they were the quintessential Oriental despots, held up as a warning to those rulers in Europe with similar aspirations. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Indeed, the interdisciplinary discourse between natural scientists and art historians is brought about by Jahangir himself to explain the advantages of a combined method, written and visual, in representing natural phenomena, and sees in it an improvement of his ancestor Babur's approach (Koch, 2009, p. 298). Ebba Koch (2009) goes on to point out that: scientists have explored the Jahangirnama for its observation(s) on geology and biology (botany, ornithology and zoology). Whereas, art historians have analysed how Jahangir directed his artists to turn his observations of natural phenomena into nature studies (Koch, 2009, p. 297).…”
Section: Source and Methodologymentioning
confidence: 99%
“…Indeed, the interdisciplinary discourse between natural scientists and art historians is brought about by Jahangir himself to explain the advantages of a combined method, written and visual, in representing natural phenomena, and sees in it an improvement of his ancestor Babur's approach (Koch, 2009, p. 298). Ebba Koch (2009) goes on to point out that: scientists have explored the Jahangirnama for its observation(s) on geology and biology (botany, ornithology and zoology). Whereas, art historians have analysed how Jahangir directed his artists to turn his observations of natural phenomena into nature studies (Koch, 2009, p. 297).…”
Section: Source and Methodologymentioning
confidence: 99%
“…The change in autobiographies from Babur to Jahangir was that Jahangir has explained with a 'combined method, written and visual, in representing natural phenomena'. 20 Another work of cursory attention exerted to credit Jahangir on and along the same lines. 21 Similarly, it gives a willing miss to the Jahangir's hunting expeditions.…”
Section: Setting the Game Of Ferocity And Innocence: Hunts Of Jahangirmentioning
confidence: 97%
“…Art historians have significantly acknowledged the same effort. 19 Art is a source to re-construct the cultural dynamism of history and associations of the empires. The change in autobiographies from Babur to Jahangir was that Jahangir has explained with a 'combined method, written and visual, in representing natural phenomena'.…”
Section: Setting the Game Of Ferocity And Innocence: Hunts Of Jahangirmentioning
confidence: 99%
“…In his first-person narrative, the Jahāngīrnāma, Jahangir demonstrated that he took delight in both natural and man-made wonder, praising the carpets of flowers that bloomed in Kashmir while also supporting a burgeoning carpet-weaving industry in Lahore. 70 Upon seeing a meadow of flowers in Kashmir, Jahangir composed a verse:…”
Section: Mughal Cultures Of Cottonmentioning
confidence: 99%